IMPLEMENTASI PEMBELAJARAN NON BERDIFERESIASI PENDIDIKAN AGAMA KRISTEN DI SDN 1 SABARU PALANGKA RAYA - Sinta Puji Astuti; Imelda Rosen; Marselina Marselina; Linta Linta (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the implementation of non-differentiated learning in Christian religious education at SDN 1 Sabaru Palangka Raya. A qualitative research method with a case study approach was used. The results show that the implementation of non-differentiated learning is effective in improving student learning outcomes and building Christian character. Factors that influence the implementation are teacher competence, infrastructure and parental support.